2008
DOI: 10.1016/j.otohns.2008.04.032
|View full text |Cite
|
Sign up to set email alerts
|

The expression of MMP‐2, MMP‐7, MMP‐9, and TIMP‐1 in chronic rhinosinusitis and nasal polyposis

Abstract: Different regulation type of activation of MMPs has been found in these two diseases. If MMP-2 expression is intense in the mucosa, then this ends with polyp formation; if MMP-7 expression is intense, it ends with CRS or stays as CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
72
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 19 publications
8
72
2
1
Order By: Relevance
“…Other studies have also shown increased levels of MMP-9 in nasal polyps [2,4,5,7,18]. Unlike other studies, we could not find statistically significant differences between MMP-9 levels of nasal polyp tissue and healthy nasal tissue.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Other studies have also shown increased levels of MMP-9 in nasal polyps [2,4,5,7,18]. Unlike other studies, we could not find statistically significant differences between MMP-9 levels of nasal polyp tissue and healthy nasal tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…Histologically, the presence of large amounts of extracellular fluid, mast cell degranulation and eosinophil has been shown [14,15]. In some studies, the excessive accumulation of ECM has been suggested as a role of nasal polyposis [2]. MMP and TIMP can be found in the extracellular tissue, and are inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations